THE RELATIONSHIP PARENTING OF RARENT WITH SPEECH DEVELOPMENT TO CHIDREN 1-3 YEARS OLD (Study In Pos Sun Early Children Education Glanggang District Beji Pasuruan) - Zumrotul Mufidah; Hindyah Ike; Anita Rahmawati (STIKES Insan Cendekia Medika Jombang, 2015)
Errors parenting parents can also influence the occurrence of speech disorders in children. In fact thereare parents who educate their children in a way or parenting which are not in accordance with the needsof children that resulted in the child being personally difficult to grow, particularly in aspects of speechdevelopment. Research purposes e the relationship between parenting parents with speech developmentof children aged 1-3 Pos early childhood years in the Garden District of Sun Glanggang Beji Pasuruan.Correlational research design (relationships and associations). Population of all the mothers who havechildren aged 1-3 years in early childhood Pos Park Sun Glanggang Beji Pasuruan District of as manyas 22 people. Sampling technique